Skill Upgrading, Self Leadership as Building Employee Performances - Nova Anggraini; Edi Sugiono; Andini Nurwulandari (International Journal of Economics and Management Sciences, 2024)
Employees who have high skill-upgrading and self-leadership will have self-confidence in their abilities. Skill-upgrading and self-leadership make employees able to organize themselves, focus on the goals they want to achieve, and have the nature of never giving up in solving problems so that it will have an impact on the resulting employee performance. The aim of writing this article is to review and synthesize existing literature related to employee performance so that it can contribute to the understanding of skill-upgrading and self-leadership which have an impact on employee performance. The data analysis technique uses qualitative analysis methods using inductive thinking patterns. Employee performance is developed properly and correctly if supported by strong skill-upgrading and self-leadership. Skill-upgrading is a way for employees to improve their quality with qualified skills, while self-leadership motivates employees to be able to lead themselves and use their creativity in carrying out a task. Skill upgrading can be done through training specifically to improve technical skills, specific expertise and knowledge that employees need in their work. Self-leadership abilities can be developed by yourself by managing time, setting goals, improving your abilities, being consistent in your activities, and doing self-reflection.